The Representation of Local Culture in Indonesian Junior High School English Textbook; When English Rings a Bell Grade VIII - Siti Marwah Ulfa (Journal of English Language Teaching and English Linguistics, 2022)
Local cultural appearances in textbooks exist through visuals and textual artifacts. Local culture is presented differently as a cultural exhibition in the textbook. This paper aims to analyze the representation of local culture contained in the textbook. This qualitative study was conducted by analyzing textbooks of junior high school grade VIII SMP/MTS approved by the Indonesian government published in 2017. This study employs Moran's (2001) cultural dimensions. Utilize two kinds of artifacts in the textbook, specifically: artifacts, images, and textual artifacts contain assignments and materials. Subsequently, four components are described visually and textually consist of product, practice, perspective, and person. Then, introducing the local culture: such as institutions, art forms, places, lives, and intellectual value. There are 8 representations of local culture in materials and exercise textbooks. There is merely found the dimensions of perspective and product and the researcher could not discover the representation of other dimensions such as persons and practices.